In Defense of a Chemical Epistemology and Ontologys - Tejada Valencia, José Reynaldo (2024)
This article presents how the philosophy of science has taken physics as the model of science, which has caused that, within the philosophy of science, all other sciences try to be reduced epistemologically and ontologically to physics. One of them, which following the development of quantum mechanics is intended to be reduced to physics, is chemistry, especially afterPaul Dirac stated that chemistry is a type of physics with highly complex mathematical equations. For chemists, understanding the structure of a chemical compound or molecule is fundamental. The molecular structure is the spatial representation of the chemical elements that make up that molecule. However, quantum mechanics cannot account for its structure, because in the quantum realm the concept of molecular structure would be nothing more than a “powerful and illuminating metaphor” with no real referent. In this article, two theses are developed, the first, that chemical structures are plausible, and the second that there is a level of chemical reality that microphysics or quantum mechanics has no possibility of either predicting or explaining.